Evaluation of renal function using cystatin C–based estimated glomerular filtration rate in patients with urothelial carcinoma treated with gemcitabine and cisplatin chemotherapy. (2nd August 2021) - Nishimura, Fumihiro; Ushijima, Tomoko; Hamada, Shinsuke; Kadowaki, Daisuke; Miyamura, Shigeyuki; Oniki, Kentaro; Saruwatari, Junji
Abstract: What is known and objective: Cisplatin‐based chemotherapy is a first‐line treatment for advanced or metastatic urinary tract urothelial carcinoma (UC). Accurate assessment of renal function is indispensable for determining cisplatin dosing to enhance the safety and effectiveness of cisplatin. The objective of this study was to assess serum cystatin C (sCys C) levels in patients with urothelial carcinoma and to explore its clinical value as a serum marker of glomerular filtration rate (GFR). Methods: This study retrospectively enrolled 18 UC patients treated with a combination of gemcitabine and cisplatin between April 2018 and November 2020. We calculated the estimated GFR (eGFR) based on serum creatinine (sCr) or sCys C and estimated Cr clearance (eCCr) based on sCr. The correlation, bias, accuracy and creatinine height index between eGFR or eCCr and measured GFR (mGFR) based on Cr clearance were calculated from urinary Cr and sCr. Results and Discussion: Estimated GFR based on sCys C correlated most strongly with mGFR. Moreover, the bias, mean error, mean absolute error and root mean square error were significantly lower in eGFRs based on sCyc C than in eGFRs based on sCr and eCCr. The correlation between eGFR based on sCys C/mGFR and creatinine height index was weaker than that between eGFR based on sCr/mGFR and creatinine height index, suggesting that sCys C was less affected by muscle mass. What is new and conclusion: In UC patients, eGFR based on sCys C reflected renal function more accurately than eGFR based on sCr, suggesting that sCys C may be useful for assessing renal function in clinical practice.